2022
DOI: 10.4103/2211-5056.354534
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and conjunctival nontuberculous mycobacteria infection

Abstract: A 64-year-old female developed refractory red-eye with itching and watery discharge 2 weeks after being injured by a comb in the left eye. It presented as diffuse pinkish thickening of the bulbar conjunctiva. Biopsy and histological examinations revealed granulomatous inflammation with microgranuloma. Acid-fast-positive bacilli were found within the tissue, which was identified by culture 5 weeks later as Mycobacterium Abscessus . The orbital computed tomography with contrast medium show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Global urban areas could increase by 1.8 to 5.9 times, and this increase is expected to be most evident in regions in Asia and Africa (Gao and O'Neill 2020). In Taiwan, urban areas increased from 1.58% of all land area in 1990 to 4.45% in 2010 (data from Chen et al 2020, and analyzed in this study). In 2010, >13% of Taiwan's land area was designated as an urban planning division area (https://ssur.cc/sAREjzv9w, accessed 1 Jul 2022) and indicated that urban areas will continue to increase.…”
Section: Figurementioning
confidence: 60%
See 1 more Smart Citation
“…Global urban areas could increase by 1.8 to 5.9 times, and this increase is expected to be most evident in regions in Asia and Africa (Gao and O'Neill 2020). In Taiwan, urban areas increased from 1.58% of all land area in 1990 to 4.45% in 2010 (data from Chen et al 2020, and analyzed in this study). In 2010, >13% of Taiwan's land area was designated as an urban planning division area (https://ssur.cc/sAREjzv9w, accessed 1 Jul 2022) and indicated that urban areas will continue to increase.…”
Section: Figurementioning
confidence: 60%
“…Precipitation is high in summer but scarce in winter, and the mean temperature ranges from 16°C (Jan) to 29°C (Jul). In 2010, urban areas in Taichung comprised 12.3% of the area, exceeding the mean percentage of urban areas in Taiwan, which was 4.5% (data reanalyzed from Chen et al 2020). Ficus ( Ficus spp.…”
Section: Study Areamentioning
confidence: 96%